Microservice Adaptability and Self-Organization of UAV-Assisted Wireless Networks in Failure Rural Scenarios - Andrés García-López; Diego Ramos-Ramos; Santiago García-Gil; José Gómez-delaHiz; Juan Manuel Murillo; Jaime Galán-Jiménez (International Journal of Distributed Sensor Networks)
Internet access remains unavailable for approximately 2 billion people in remote areas, limiting their access to essential services such as healthcare and education. This paper presents a UAV-based wireless network architecture combined with a microservice model to ensure the dynamic deployment of IoT applications in rural environments. To address challenges arising from UAV failures and battery depletion, we propose an energy-aware, self-organizing mechanism integrated with a UAV controller for real-time network reconfiguration. Simulation results over realistic rural scenarios show that the proposed approach successfully satisfies over 90% of IoT application requests, maintains high service continuity despite UAV failures, and demonstrates strong scalability under increasing workloads. These findings highlight the effectiveness and resilience of our solution for reducing the digital divide in underserved regions.